DEVELOPMENT OF AUDIO VISUAL LEARNING MEDIA ON THE MATERIAL OF BLACK GLUTINOUS RICE GROWTH (Oryza sativa L var.glutinous) IN VITRO AT SMK AL HIDAYAH WULUHAN - Sudiarti, Diah; Wulandari, Windarti; Bukhori, Imam (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2024)
The world of education in Indonesia always follows the era of development, whereas currently, education follows the digital era where every school requires teachers as educators to develop the learning media used. Learning media is a tool used to improve school learning quality. Supportive learning media allows students to receive material well. This audio-visual learning media research uses the research and development method (Research of Development), the research model used is the Plomp 2013 development model, which includes 3 steps, namely the Analysis stage (Analysis), the Prototype Design and Development stage, and the Evaluation stage, the evaluation stage includes validation of material experts, validation of media experts, and practicality sheets, namely questionnaires given to teachers and students. The results of the research on the development of audio-visual learning media obtained an average score of 84% with the category (very valid) in the validation of material experts, and an average score of 83% with the category (very valid) in the validation of media experts, obtained an average score of 89.3% in the practicality test for teachers with the category very practical, and obtained an average score of 84% in the readability test by students with the category (very practical).